Vertical Hot-Melt Extrusion: The Next Challenge in Innovation - Maël Gallas; Ghouti Medjahdi; Pascal Boulet; Victoire de Margerie (Pharmaceutics, 2025)
Background/Objectives: Hot-melt extrusion (HME) has become a key technology in pharmaceutical formulation, particularly for enhancing the solubility of poorly soluble Active Pharmaceutical Ingredients (APIs). While horizontal HME is widely adopted, vertical HME remains underexplored despite its potential benefits in footprint reduction, feeding efficiency, temperature control, and integration into continuous manufacturing. This study investigates vertical HME as an innovative approach in order to optimize drug polymer interactions and generate stable amorphous dispersions with controlled release behavior. Methods: Extrusion trials were conducted using a vertical hot-melt extruder developed by Rondol Industrie (Nancy, France). Acetylsalicylic acid (ASA) supplied by Seqens (Écully, France) was used as a model API and processed with Soluplus® and Kollidon® 12 PF (BASF, Ludwigshafen, Germany). Various process parameters (temperature, screw speed, screw profile) were explored. The extrudates were characterized by powder X-ray diffraction (PXRD) and small-angle X-ray scattering (SAXS) to evaluate crystallinity and microstructure. In vitro dissolution tests were performed under sink conditions using USP Apparatus II to assess drug release profiles. Results: Vertical HME enabled the formation of homogeneous amorphous solid dispersions. PXRD confirmed the absence of residual crystallinity, and SAXS revealed nanostructural changes in the polymer matrix influenced by drug loading and thermal input. In vitro dissolution demonstrated enhanced drug release rates compared to crystalline ASA, with good reproducibility. Conclusions: Vertical HME provides a compact, cleanable, and modular platform that supports the development of stable amorphous dispersions with controlled release. It represents a robust and versatile solution for pharmaceutical innovation, with strong potential for cost-efficient continuous manufacturing and industrial-scale adoption.